Development model of halal concept integration based on sustainable village tourism - Aslamiyah, Suaibatul; Aulia Rahmi, Vembri (Journal of Halal Science and Research, 2025)
Village tourism with halal tourism development is a tourism asset based on rural potential that can be empowered and developed as a tourism product to attract tourist visits and impact equitable development at the village level and the community's economy. This study aims to produce a halal tourism concept as an innovation in developing tourism activities in the Lontar Sewu tourist village to realize people's welfare during the Industrial Revolution. The method is qualitative and interpretative, and it is located in Hendrosari Village, Gresik Regency. Through content analysis, content, and strategic matrix instrument, it was found that the concept of a halal tourism model based on sustainable village tourism in Lontar Sewu Tourism, Hendrosari Village, Gresik Regency is based on the principle of maqashid sharia. Examining all the results of the matrix above, it can be found that the aspects of Hifz al-Din, Hifz al-Nafs, and Hifz al-Aql are the most important in the integration of the halal concept because they have the highest and most implementation value.   Keywords: Halal tourism, Maqashid sharia, Sustainable development, Strategy.